Adult presentation of X‐linked Conradi‐Hünermann‐Happle syndrome. (2nd April 2015) - Posey, Jennifer E.; Burrage, Lindsay C.; Campeau, Philippe M.; Lu, James T.; Eble, Tanya N.; Kratz, Lisa; Schlesinger, Alan E.; Gibbs, Richard A.; Lee, Brendan H.; Nagamani, Sandesh C.S.
Abstract : Conradi‐Hünermann‐Happle syndrome, or X‐linked dominant chondrodysplasia punctata type 2 (CDPX2), is a genodermatosis caused by mutations in EBP . While typically lethal in males, females with CDPX2 generally manifest by infancy or childhood with variable features including congenital ichthyosiform erythroderma, chondrodysplasia punctata, asymmetric shortening of the long bones, and cataracts. We present a 36‐year‐old female with short stature, rhizomelic and asymmetric limb shortening, severe scoliosis, a sectorial cataract, and no family history of CDPX2. Whole exome sequencing (WES) revealed a p.Arg63del mutation in EBP, and biochemical studies confirmed a diagnosis of CDPX2. Short stature in combination with ichthyosis or alopecia, cataracts, and limb shortening in an adult should prompt consideration of a diagnosis of CDPX2. As in many genetic syndromes, the hallmark features of CDPX2 in pediatric patients are not readily identifiable in adults. This demonstrates the utility of WES as a diagnostic tool in the evaluation of adults with genetic disorders. © 2015 Wiley Periodicals, Inc.